Fractional Flow Reserve-Guided Hybrid Coronary Revascularization in Multi-Vessel Coronary Arteries Disease - Y. Y. Stukov; S. A. Rudenko; A. Yu. Gavrylyshyn; M. L. Rudenko; S. V. Salo; A. V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Coronary artery bypass grafting without cardiopulmonary bypass (OPCABG) as a minimally invasive cardiac surgery (MICS) procedure has been used increasingly to treat coronary artery disease. We present our experience using off-pump minimally – invasive direct coronary artery bypass grafting (OPMIDCAB) and fractional flow reserve (FFR) – guided percutaneous coronary interventions (PCI) strategy for coronary revascularization.Purpose. Presentation of our experience in FFR – guided hybrid coronary revascularization in patients with multi – vessel coronary artery disease.Conclusion. A hybrid procedure that changes a conventional CABG of all stenotic arteries, into a FFR – guided PCI is an appealing way to minimize the risk of complex heart surgery, combining positive outcomes of CABG along with low stent restenosis and thrombosis rates compared to venous grafts.